Antimicrobial Peptides in Human Disease: Therapeutic Approaches. Second of Two Parts - Magrone, Thea; Russo, Matteo A.; Jirillo, Emilio (Current Pharmaceutical Design, 2018)
Antimicrobial Peptides (AMPs) are produced by a variety of human immune and non immune cells in health and disease. In virtue of their antimicrobial activity, AMPs have been exploited in human disease and here this aspect will extensively be described. AMPs in comparison to antibiotics possess a larger spectrum of antimicrobial activity without inducing microbial resistance. Therefore, their use in the course of antibiotic-resistant infections is justified. AMP activity in early life, in the airways, in the oral and gastro-enteric system, in the skin and in the female reproductive tract, respectively, will be elucidated. In addition, the use of AMPs in sepsis will be discussed due to the frequency of this pathological condition characterized by multiple organ dysfunctions. Finally, the evidence that AMPs represent valid substitutes of antibiotics will be provided and a series of novel substances able to reinforce the innate immune response in different clinical settings will be discussed.
Keywords: antibiotic-resistant infections